Implementasi Peraturan Gubernur Nomor 54 Tahun 2017 Tentang Penerapan Disiplin Jam Kerja di Biro Pemerintahan dan Perbatasan Sekretariat Daerah Provinsi Kepulauan Riau dalam Penggunaan Mesin Pemindai Sidik Jari (Fingerprint Scanner) - RIAU SUJARWANI; Reza Indra Pratama (STISIPOL Raja Haji, 2021)
Working hour discipline is an activity that must be carried out by all employees. The application of the discipline of working hours is regulated in Governor Regulation No.54 of 2017. The application of fingerprint attendance is made to make it easier for superiors to see the level of discipline for the attendance of each employee. So far, in manual attendance, superiors or other employees who see attendance cannot see the level of discipline of employee attendance, because in manual attendance there is no information about when the employee comes and goes home, employees can join other days or leave absences to other employees. This makes it difficult for superiors to impose sanctions in accordance with Governor Regulation No.54 of 2017 concerning Working Hours Discipline. The purpose of this study is to determine the implementation of PERGUB No.54 of 2017 concerning the Application of Working Hours Discipline at the Government Bureau and Border Regional Secretariat of the Riau Islands Province in the Use of Fingerprint Scanner. The population will be taken from The Government Bureau and Border Regional Secretariat of the Riau Islands Province with total population 45 employees. The Research type is a qualitative research with descriptive qualitative analysis technique. Sources and types of data are using primary and secondary data, with data collection techniques and tools using interview techniques. The results of this study are from the Governor’s Regulation Number 54 on 2017 about Implementation of working time discipline at the Government Bureau and Border Regional Secretariat of the Riau Islands Province is considered Effective because the Employees are able to do and implemented the Governor’s Regulation Number 54 as stated in the Regulation itself.